The Relationship Between Mileage, Parity, And Occupation With The Frequency Of Antenatal Care Visits According To Standards In The Work Area Of The Wanaya Public Health Center, Lahat Regency In 2021 - Novi Meryanti; Helni Anggraini; Sendy Pratiwi Ramadhani (Science Midwifery, 2022)
ANC or antenatal care is services provided by health workers according to the right standard for pregnant women to check their pregnancy condition. The purpose of this research is to know the relationship between mileage, parity, and profession with the frequency of antenatal care visit according to standard in the working area of ​​Wanaraya Public Health Center, Lahat Regency 2021. This research is observational and analytic characterized with cross sectional approach. The population of this research was maternity women in the working area of ​​Wanaraya Public Health Center, Lahat Regency from January to July 2021 with total number was 45 people. The sampling technique where all of the population became sample with total number was 45 people. The statistical test with chi-square result showed that p value of mileage 0.003 (p<0.05), parity 0, 025 (p<0.05), and professions 0.001 (p<0.05). In conclusion , there was a relationship between mileage , parity, and profession with the frequency of antenatal care visite according to standard in Wanaraya Public Health Center, Lahat Regency 2021.